2013
DOI: 10.1159/000353444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia in Japan: A Systematic Review

Abstract: Background/Aims: The actual prevalence of dementia in Japan as well as the changes in the prevalence are not well known. Therefore, we undertook a systematic review to collect evidence regarding the prevalence of dementia in Japan. Methods: For this systematic review, we searched 2 electronic databases to identify cross-sectional or repeated cross-sectional studies with data regarding the study population, study location, diagnostic criteria, and prevalence of dementia. Results: Twenty-one studies were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Recent studies suggest that changes have been occurring, with decreases in the agespecific incidence or prevalence in the United States, United Kingdom, Sweden, the Netherlands, France, and Canada, probably reflecting reduced exposure to risk factors or increased resilience to cognitive decline, but in others, for example, Japan and China this is not the case (Chan et al 2013;Okamura et al 2013). Identifying and modifying risk could translate to a huge benefit for societies, individuals, and health care systems.…”
Section: Prevention Of Dementia Recommendationsmentioning
confidence: 99%
“…Recent studies suggest that changes have been occurring, with decreases in the agespecific incidence or prevalence in the United States, United Kingdom, Sweden, the Netherlands, France, and Canada, probably reflecting reduced exposure to risk factors or increased resilience to cognitive decline, but in others, for example, Japan and China this is not the case (Chan et al 2013;Okamura et al 2013). Identifying and modifying risk could translate to a huge benefit for societies, individuals, and health care systems.…”
Section: Prevention Of Dementia Recommendationsmentioning
confidence: 99%
“…[5][6][7] An independent study has also reported recent increases in the prevalence of dementia in Japan. 8 The higher medical expenditures incurred by nursing home residents with advanced dementia in the USA was found to be influenced by the lack of do not hospitalize orders, tube feeding, and not living in special care units. 9 In Germany, annual healthcare spending by dementia patients was reported to be three times that of patients without dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the US and Europe, recent reviews have reported an increasing trend of dementia prevalence in Japan over last decades [21,22]. However, this finding might be driven by variation of study methods and characteristics of study populations over time [21,23].…”
Section: High-income Countries: Western Europe North America and Japanmentioning
confidence: 99%
“…However, this finding might be driven by variation of study methods and characteristics of study populations over time [21,23]. Despite potential bias in study designs and analysis methods, some studies applying the similar study methods in the small areas reported stability of dementia prevalence from 1980s to 1990s but with high prevalence in surveys after 2000 [22,24,25]. The prevalence of dementia in Japan could have potentially increased in recent 8-10 years but have been relatively stable before 2000.…”
Section: High-income Countries: Western Europe North America and Japanmentioning
confidence: 99%